DAMPAK KEBIJAKAN REKLAMASI PANTAI BOULEVARD PADA MASYARAKAT NELAYAN KECAMATAN SARIO KOTA MANADO - WOWOR, CHRISTOVEL; DENGO, SALMIN; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
The policy of beach reclamation on Boulevard Manado which is quite extensive has caused some problemsor incompatibilities in terms of the socio-economic conditions of fishing communities around thereclamation area. After the coastal reclamation policy was implemented it turned out to have an impact onthe surrounding fishing community who had difficulty in finding fish and meeting their needs. So in gettingthe formulation of the problem of how the socio-economic impacts felt by the fishing community due to thepolicy of coastal reclamation on Boulevard Manado, especially in Sario District. The purpose of thisresearch is to provide an overview and analyze the socio-economic impacts felt by fishing communities asan impact arising from the policy of coastal reclamation on Boulevard Manado. This research wasconducted to evaluate the impact of the coastal reclamation policy. In evaluating the impact of this policy,the researcher used the theory of impact evaluation or summative evaluation with the eveluation method ofRossi and Freeman, then used the Act and a number of other advocate theories. This type of research isdescriptive with a qualitative approach.Keywords: Policy, Coastal Reclamation, Impact.